Photobiomodulation in oral medicine: a review. Issue 2 (26th February 2015) - Pandeshwar, Padma; Roa, Mahesh Datta; Das, Reshma; Shastry, Shilpa P.; Kaul, Rachna; Srinivasreddy, Mahesh B.
Abstract: Photobiomodulation (PBM) or low‐level laser therapy (LLLT) in dentistry is an evolving science, with an increasing number of controlled clinical studies exploring its potential as a treatment modality. The present study provides an outline of the biologic mechanism of PBM and summarizes the findings of clinical studies of PBM for specific applications in oral medicine. Controversies and drawbacks associated with PBM, which require further research, are also identified. Current literature reports the potential of PBM in various applications in oral medicine. Furthermore, well‐documented research confirms its efficacy in certain conditions, such as oral mucositis, recurrent herpes simplex infection, and burning mouth syndrome. The absence of any reported adverse effects is an advantage over conventional therapeutic modalities. While PBM has proved to be effective for some specific applications, it is not a panacea. The paucity in standardized studies, coupled with ambiguity over the laser parameters, has limited its credibility as a therapeutic modality.